Skin Manifestations of Diabetes Mellitus - Kiran Fatima , Aqsa Naheed , Shazia Amir Khan (Journal of Rawalpindi Medical College, 2018)
Background: To analyze skin manifestations in patients with diabetes mellitus Methods: This cross sectional study was conducted on 100 consecutive patients of Diabetes Mellitus type 1 &2, either attending the out-patients departments of Dermatology and Medicine or admitted in medical wards of Cantonment General Hospital, Rawalpindi from 1st January 2017 to 30th June 2017. Both male and female patients aged between 15-80 years were included in the study. Results: Out of hundred patients, skin changes were present in 64%. The common disorders were skin infections in 43 patients, pruritis in 17, and skin tags in 15 patients. Other manifestations were lichen planus in 5, diabetic foot in 5, acanthosis nigricans in 4, eruptive xanthomas in 3, eczema in 3, vitiligo in 2, diabetic dermopathy in 1, xerosis in 1 and psoriasis in 1 patient. Conclusion: Skin involvement is quite common in diabetes. It can manifest as first sign or may manifest at any time during the course of disease so it is important to identify and appropriately treat these patients.